How we treat advanced stage cutaneous T‐cell lymphoma – mycosis fungoides and Sézary syndrome. (14th May 2021) - Sethi, Tarsheen K.; Montanari, Francesca; Foss, Francine; Reddy, Nishitha
Summary: T‐cell lymphomas (TCLs) constitute a rare subset of non‐Hodgkin lymphomas, with mycosis fungoides/Sézary syndrome (MF/SS) being the most common subtype of cutaneous TCLs (CTCLs). Considered an incurable but treatable disease, MF/SS management presents several challenges including diagnostic delays, debilitating effect on patients' quality of life, need for several lines of therapies, multidisciplinary care and cumulative drug toxicities limiting duration of use. The present review intends to provide an overview of the recent advances in our understanding of the biology of CTCL and how these are being leveraged to provide additional treatment options for management of advanced and recurrent disease. In addition, the discussion of the different modalities of treatment is summarised to further outline the importance of multidisciplinary care and early referral to CTCL centres.